SOIL AND SOIL EROSION MEASURES OF UGAM-CHOTOKOL NATIONAL PARK: PROBLEMS AND CONSERVATION STRATEGIES (Scientific journal of the Fergana State University, 2024)
The Ugam-Chatkal National Park, located in the Tien-Shan Mountains of Uzbekistan, is a natural resource of biological diversity and ecological importance. The park contains many ecosystems, from natural forests to alpine meadows. The rational use of natural resources and keeping the environment in good condition is the basis of a sustainable ecosystem. An integral component of these ecosystems is soil, which plays a crucial role in supporting the region's rich flora and fauna. In this article, we will enter the fascinating world of the soils of the Ugam-Chatkal National Park and study their types, characteristics and importance. In addition, the park explores soil erosion, the causes and characteristics of erosion, and additional nature conservation strategies to mitigate the environmental problem.